2013
DOI: 10.1186/1471-2288-13-56
|View full text |Cite
|
Sign up to set email alerts
|

How are European birth-cohort studies engaging and consulting with young cohort members?

Abstract: BackgroundBirth cohort studies, where parents consent for their child to be enrolled in a longitudinal study prior to or soon after birth, are a powerful study design in epidemiology and developmental research. Participation often continues into adulthood. Where participants are enrolled as infants, provision should be made for consent, consultation and involvement in study design as they age. This study aims to audit and describe the extent and types of consultation and engagement currently used in birth coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Although influential birth cohort studies have been established in Europe, [ 36 , 37 ] most cohort studies in the US have enrolled adults, and older adults at that. Although some US prospective cohort studies have begun in childhood, span a long period of time, and have a focus on health (Wisconsin Longitudinal Study), many have only limited health measures, or the current age for adult disease follow up remains relatively young (Add Health, National Longitudinal Study of Youth; Early Childhood Longitudinal Study; Panel Study of Income Dynamics; National Children’s Study).…”
Section: Discussionmentioning
confidence: 99%
“…Although influential birth cohort studies have been established in Europe, [ 36 , 37 ] most cohort studies in the US have enrolled adults, and older adults at that. Although some US prospective cohort studies have begun in childhood, span a long period of time, and have a focus on health (Wisconsin Longitudinal Study), many have only limited health measures, or the current age for adult disease follow up remains relatively young (Add Health, National Longitudinal Study of Youth; Early Childhood Longitudinal Study; Panel Study of Income Dynamics; National Children’s Study).…”
Section: Discussionmentioning
confidence: 99%
“…Such techniques include mail surveys, telephone surveys, birthday cards, sending mobile phone reminders and newsletters [18]. Follow-up rates of cohorts in developing populations with conditions in contrast to the ABC study are similar or higher than our study.…”
Section: Discussionmentioning
confidence: 47%
“…According to the study published by Lucas et al [9], most European birth cohort studies are working to increase the participation rate of cohort subjects, and it has been reported that efforts have been made to increase participation through the operation of “research websites.” The research teams of the cohorts sent newsletters, cards, and study results to subjects in order to maintain contact and some studies even utilized social networks, but there did not appear to be much active communication, such as taking the opinions of the subjects into account. Analysis in this study found that the following are barriers that affect the continuous participation in surveys: lack of trust in the quality of the study, ethical limitations, lack of resources, absence of priorities, negative experience in previous studies, etc.…”
Section: Discussionmentioning
confidence: 99%